87 Evolution of Atrial Fibrillation. (16th September 2019) - Meagher, Marykate; Noone, Imelda; Davey, Naomi; Cassidy, Tim
Abstract: Background: Atrial Fibrillation (AF) is a common cardiac arrhythmia and a well-established risk factor for stroke with its prevalence increasing with age. AF related strokes are associated with increased mortality and morbidity however the risk of stroke is reduced by almost 70% by oral anticoagulation (OAC). Methods: Analysis of data using SPSS allowed us to identify all acute stroke patients admitted in 2018 with AF. We compared data on patients who were admitted with known AF and those who were newly identified with AF and looked at their outcomes. Results: 373 stroke patients admitted, of which 108(29%) patients had AF, mean age 79. 68(63%) had known AF and 40(37%) had a new diagnosis of AF. 52(76.5%) of the known AF were on an OAC (11 on warfarin) and 40(78%) on a Non- Vitamin K antagonist oral anticoagulant (NOAC). 16 patients (23.5%) with known AF were not anticoagulated on admission. (Reasons for no OAC-3 had a history of previous intracerebral haemorrhage (ICH). 2 a history of bleeding and 1 a history excess alcohol). 10 patients were on antiplatelet therapy and were subsequently anticoagulated on discharge. 33(48.5%) of the known AF were discharged home versus 15(37.5%) in the new AF cohort and while mortality was higher in the known AF, there were more patients in the new AF cohort 14(35%) that required long term care compared with 3(4%) in the known AF cohort which not only indicates the severity of their stroke but also suggests that if AF had been detected and treated sooner their outcome may have been very different. Conclusion: There has been a significant increase in primary prevention practices for AF and this is reflected in the number of stroke patients presenting with known AF on a NOAC, however more needs to be done as there are still patients who have AF that are not being anticoagulated in the community.